First principles study of electronic and optical properties and photocatalytic performance of GaN–SiS van der Waals heterostructure. Issue 52 (7th October 2021) - Ullah, S. S.; Farooq, M.; Din, H. U.; Alam, Q.; Idrees, M.; Bilal, M.; Amin, B.
Abstract : The two dimensional GaN–SiS van der Waals heterostructure is a promising candidate for optoelectronic and photocatalytic water splitting. Abstract : The vertical stacking of two-dimensional materials via van der Waals (vdW) interaction is a promising technique for tailoring the physical properties and fabricating potential devices to be applied in the emerging fields of materials science and nanotechnology. The structural, electronic and optical properties and photocatalytic performance of a GaN–SiS vdW heterostructure were explored using first principles calculations. The most stable stacking configuration found energetically stable, possesses a direct staggered band gap, which is crucial for separating photogenerated charged carriers in different constituents and is efficacious for solar cells. Further, the charge transfer occurred from the SiS to GaN layer, indicating that SiS exhibits p-type doping in the GaN–SiS heterobilayer. Interestingly, a systematic red-shift was observed in the optical absorption spectra of the understudy heterobilayer system. Moreover, the conduction band edge and valence band edge of the monolayers and corresponding heterostructure were located above and below the standard redox potentials for photocatalytic water splitting, making these systems promising for water dissociation for hydrogen fuel production. The results provide a route to design the GaN–SiS vdW heterostructure for the practical realization of next-generation light detection and energy harvesting devices.